Correlation of Clinical Aqueous Flare Grading to Semi-Automated Flare Measurements Using Laser Flare Photometry. (17th November 2022) - Halim, Muhammad Sohail; Hasanreisoglu, Murat; Onghanseng, Neil; Tran, Anh N.T.; Hassan, Muhammad; Yilmaz, Mervenur; Segawa, Asadu; Gurelik, Gokhan; Afridi, Rubbia; Ormaechea, Maria Soledad; Uludag, Gunay; Kesim, Cem; et al.
ABSTRACT: Purpose: To compare laser flare photometry (LFP) measurements of aqueous flare with Standardization of Uveitis Nomenclature (SUN) and modified SUN grading. Methods: In this prospective study with multicenter design, uveitis patients were classified according to SUN and modified SUN grading scales. LFP was performed with Kowa FM-700 flaremeter. Mean LFP values were compared with SUN and MSUN scores. Results: The study included 475 LFP measurements, of which 216, 48, 150, 31, 28 and 2 had 0, 0.5+, 1+, 1.5+, 2+ and 3+ flare, respectively. LFP values were significantly different between each two consecutive steps for both clinical gradings (all P < .05). Cut-off values for modified SUN grading steps were defined as 5.7, 9.7, 15.7 and 43.2 for 0/0.5+, 0.5+/ 1+, 1+/1.5+ and 1.5/2+ borders of clinical flare, respectively. Conclusions: LFP proves to be an objective measurement in analyzing aqueous flare comparable to both SUN and MSUN clinical grading systems.